Effect of Tick and Lice on Some Blood Constitute and Trace elements of Local Black Goat in Sulaimani, Kurdistan Region of Iraq - Abdalrahman, Bawan Mustafa; Mustafa, Bahzad Hama Salih (Kurdistan Journal of Applied Research, 2018)
In this study isolated 100 adult female of local black goat (Capra hircus) examined in spring and fall season for Tick and Lice investigations, then divided into two groups: 50 infested goats with ectoparasite and 50 non-infested goats. Three species of ticks (Rhipicephalus sanguinus, R. turanicus and R. bursa) and one species of lice (Bovicola caprae) were observed. Biochemical values (serum proteins and some trace elements) analyzed, in infested goats emerges decline in serum protein value 7.12±0.08 µg/dl, albumin value 4.12±0.03 µg/dl and increase of globulin value 3.04±0.09 µg/dl, in serum protein and globulin values shows not significance differences, while described highly significance differences in albumin value at p?0.01, when compared to control goats. In trace elements decline of zinc level 48.97±1.20 µg/dl and copper level 114.15±3.75 µg/dl levels with a highly significant differences at p?0.01 in infested goats when compare to control goats. It is observed that mixed infestation has much effects than tick or lice infestation on goats, which led to reduction in serum protein value 6.89±0.20 µg/dl, albumin value 4.11±0.09 µg/dl and raise in globulin value 3.10±0.11 µg/dl without any significance differences, also noticed insignificant declines in zinc level 45.67±2.40 µg/dl, while decrease in copper level 99.33±9.86 µg/dl significantly at p?0.05.